2023
DOI: 10.1097/js9.0000000000000319
|View full text |Cite
|
Sign up to set email alerts
|

Indocyanine green fluorescence imaging to localize insulinoma and provide three-dimensional demarcation for laparoscopic enucleation: a retrospective single-arm cohort study

Abstract: Background: Indocyanine green (ICG) fluorescence imaging is a new technology that can improve the real-time location of tumor edges and small nodules during surgery. However, no study has investigated its application in laparoscopic insulinoma enucleation. This study aimed to evaluate the feasibility and accuracy of this method for intraoperative localization of insulinomas and margin assessment during laparoscopic insulinoma enucleation. Materials and Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
(40 reference statements)
0
0
0
Order By: Relevance
“…In 2016, Paiella, an Italian scholar, rst applied the indocyanine green imaging technology in pancreatic neuroendocrine tumor surgery [21] ; Kou et al reported a case of intraoperative localization of pancreatic insulinoma using indocyanine green uorescence imaging as a relatively safe and simple method [22] . A retrospective single-arm cohort study by Prof. Chihua Fang et al suggests that indocyanine green uorescence imaging can guide surgeons to locate tumors effectively during laparoscopic insulinoma resection [23] . In this study, we found that indocyanine green uorescence imaging is more effective than laparoscopic insulinoma resection.…”
Section: Discussionmentioning
confidence: 99%
“…In 2016, Paiella, an Italian scholar, rst applied the indocyanine green imaging technology in pancreatic neuroendocrine tumor surgery [21] ; Kou et al reported a case of intraoperative localization of pancreatic insulinoma using indocyanine green uorescence imaging as a relatively safe and simple method [22] . A retrospective single-arm cohort study by Prof. Chihua Fang et al suggests that indocyanine green uorescence imaging can guide surgeons to locate tumors effectively during laparoscopic insulinoma resection [23] . In this study, we found that indocyanine green uorescence imaging is more effective than laparoscopic insulinoma resection.…”
Section: Discussionmentioning
confidence: 99%